The open door swings both ways: Australia, China and the British World System, c.1770-1907. - Mountford, B (2012)
This doctoral thesis considers the significance of Australian engagement with China within British imperial history between the late-eighteenth and early-twentieth centuries. It sets out to explore the notion that colonial and early-federation Australia constituted an important point of contact between the British and Chinese Empires. Drawing on a long tradition of imperial historiography and recent advances in British World and Anglo-Chinese history, it utilises extensive new archival research to add a colonial dimension to the growing body of scholarship on the British Empire’s relations with Qing China. In doing so, it also seeks to contribute to a better understanding of the internal dynamics and external relations of Britain’s late-Victorian and Edwardian Empire. The following chapters centre around two overarching historical themes. The first is the interconnection between Chinese migration to Australia and the protection of British mercantile and strategic interests in the Far East as imperial issues. The second is the relationship between Australian engagement with China and the development of the idea of a Greater Britain. Each of these themes throws up a range of fascinating historical questions about the evolving character of Britain’s late-Victorian and Edwardian Empire, the inter-relation of its various parts and its ability to navigate the shifting winds of political and economic change. Taken together, they shed new light not only on Anglo-Australian, Anglo-Chinese and Sino-Australian history, but also serve to illuminate a series of triangular relationships, connecting the metropolitan, Far Eastern and Australian branches of the British Empire.